Fatigue in acromegaly patients: a scoping review - Wang, Wei; Han, Xiaoxu; Huang, QingHua (Frontiers in Endocrinology, 2025)
PurposeThis scoping review systematically examines current evidence on fatigue in acromegaly patients, with a particular focus on incidence, risk factors, hazards, assessment tools and therapeutic interventions, to inform evidence-based interventions aimed at improving rehabilitation outcomes.MethodsA scoping review was conducted following the PRISMA-ScR guidelines. We systematically searched five international databases (PubMed, Embase, CINAHL, Web of Science, and the Cochrane Library) and three Chinese databases (CNKI [China National Knowledge Infrastructure], WanFang, and Sinomed) from their inception through June 21, 2025. The inclusion criteria included original studies investigating fatigue manifestations in patients with acromegaly, including epidemiological studies, psychometric validation reports, and intervention trials. The exclusion criterion was articles focused exclusively on pharmacological or surgical interventions without fatigue assessment. Two independent researchers performed literature screening, data extraction, and quality appraisal via standardized protocols.ResultsA total of 20 studies were included (all English-language publications). The prevalence of fatigue in acromegaly patients is high, ranging from 49% to 92%. Objective fatigue assessment tools primarily involve electromyography (EMG) and isokinetic dynamometry of the knee joint. Subjective fatigue was evaluated with patient self-reports. Factors that influence fatigue in these patients include demographic characteristics, sociological factors, sleep disturbances, comorbidities, and disease-specific factors. Interventions included aerobic exercise, rehabilitation therapist-guided home rehabilitation programs, and cognitive behavioral therapy.ConclusionThis scoping review underscores the need for future large-scale longitudinal studies on fatigue in acromegaly. Priority areas include identifying predictive markers, understanding pathophysiological mechanisms, evaluating targeted interventions, and developing standardized assessment tools to improve early recognition and management.